Análise teórico-experimental dos erros envolvidos na determinação da umidade da madeira por atenuação de radiação gama - de Aguiar , O; Ferraz , E S B (Revista Ceres, 2025)
The sources of errors in wood moisture determination by gamma-ray attenuation were sought. Equations were proposed for determining errors and for ideal sample thickness.